Reproducing Development’s Trusteeship and Discursive Power - Lie, Jon Harald Sande (Consilience, 2016)
Development aid is characterised by an inherently asymmetry between donor and recipient institution. Despite regular aid reforms and bold ambitions to change this relation, the asymmetry seems to persist. Inspired by post-development theory, and drawing on both a review of development theory and ethnographic fieldwork within the World Bank, this article argues that the lopsided aid-relations are contineously being reproduced through the formation of development expert knowledge within authoritative donor communities. Here, contemporary konwledge/power formations shape and are shaped by historically embedded structures and epistemic communities that benefit the donor’s need for legible and operational knowledge, being knowledge of a particular kind. Hence, top-down approaches to development planning are reproduced at the cost of participatory, bottom-up ones, as per the official order and rhetoric.